Treatment of Barrett’s esophagus with a novel focal cryoablation device: a safety and feasibility study - Schölvinck, Dirk W.; Künzli, Hannah T.; Kestens, Christine; Siersema, Peter D.; Vleggaar, Frank P.; Canto, Marcia Irene; Cosby, Hilary; Abrams, Julian A.; Lightdale, Charles J.; Tejeda-Ramirez, Elizabeth; DeMeester, Steven R.; Greene, Christine L.; Jobe, Blair A.; Peters, Jeff; Bergman, Jacques J. G. H. M.; Weusten, Bas L. A. M. (Endoscopy, 2015)
Background and aims: Currently, eradication of Barrett’s epithelium is preferably achieved using radiofrequency ablation (RFA) or spray cryoablation (SCA). However, both modalities suffer from drawbacks such as the need for sizing, multiple deployment steps, large controller units (RFA), imprecise dosing and need for gas-venting (SCA). The new Cryoballoon Focal Ablation System (CbFAS) may address these limitations. This study assessed the safety, feasibility, and dose response of the CbFAS in patients with flat Barrett’s epithelium with or without dysplasia.Patients and methods: In this multicenter, prospective non-randomized trial, 39 patients were each treated with one or two ablations of 6, 8, or 10 seconds. Symptoms were assessed immediately and 2 days post-cryoablation. Follow-up endoscopy was performed 6 – 8 weeks post-procedure to assess response. Outcome parameters were incidence of adverse events, pain, esophageal stricture formation, and ablation response by cryogen dose.Results: Of 62 ablations, 56 (10 with 6 seconds, 28 with 8 seconds, 18 with 10 seconds) were successfully performed. Six ablations failed because of device malfunction (n = 3) and procedural or anatomic issues (n = 3). Median procedure time was 7 minutes (interquartile range [IQR] 4 – 10). No major adverse events occurred; six patients experienced a minor mucosal laceration requiring no intervention. Mild pain was reported by 27 % of patients immediately after cryoablation and by 14 % after 2 days. No strictures were evident at follow-up. Full squamous regeneration was seen in 47 treated areas (6 [60 %] of the 6-second areas; 23 [82 %] of the 8-second areas; 18 [100 %] of 10-second areas).Conclusions: Focal cryoablation of Barrett’s epithelium with the CbFAS is feasible and safe, resulting in squamous regeneration in the majority of patients.